A brief overview of syllable stress placement in English vocabulary - Tuan, Dang Anh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2021)
How to correctly pronounce an English word seems to be a serious problem to most learners. This requires a perfect combination of sounds and stress in the word, and stress is supposed to be more important than sounds. The correct placement of word stress or syllable stress is essential for the learner's use and perception of English. For this reason, the paper may select and suggest some stress rules in the hope that the learners may feel useful for making the correct syllable stress in an English word. However, only main stress or primary stress in simple words is discussed, and the stressed syllables are presented in boldface letters throughout this paper.